Wage Inequality and Wage Mobility in Europe - Ronald Bachmann; Peggy Bechara; Sandra Schaffner (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
Using data from the European Union Statistics on Income and Living Conditions (EU-SILC), this paper investigates wage inequality and wage mobility in Europe. Decomposing inequality into within and between group inequality, we analyse to what extent wage inequality and mobility can be explained by observable characteristics. Furthermore, we investigate which individual and household characteristics determine transitions within the wage distribution. Finally, we examine the importance of institutions for wage inequality, wage mobility, and wage transitions. We find that overall, mobility reduces wage inequality. While a large part of wage inequality is due to unobservable characteristics, the equalizing effect of mobility mainly occurs within groups. Furthermore, both personal and household characteristics play an important role for wage transitions. Finally, our findings reveal large cross-country differences across Europe, which are partly linked to the institutional set-up of the national labour markets. – – Auf Grundlage der Statistik der Europäischen Union über Einkommen und Lebensbedingungen wird in diesem Papier die Lohnungleichheit und die Lohnmobilität in Europa untersucht. Eine Zerlegung der Ungleichheit in Ungleichheit innerhalb und zwischen Bevölkerungsgruppen liefert Erkenntnisse darüber, inwiefern Lohnungleichheit und -mobilität durch beobachtbare Eigenschaften erklärt werden können. Darüber hinaus werden die Bedeutung von individuellen und Haushaltscharakteristika für Transitionen innerhalb der Lohnverteilung analysiert. Letztlich wird der Zusammenhang von Institutionen mit Lohnungleichheit, Lohnmobilität und Lohntransitionen untersucht. Die Ergebnisse der Analyse lauten wir folgt. Mobilität verringert Lohnungleichheit. Obwohl ein hoher Anteil der Lohnungleichheit auf unbeobachtbare Faktoren zurückzuführen ist, findet der ausgleichende Effekt von Mobillität hauptsächlich zwischen den Bevölkerungsgruppen statt. Zudem spielen sowohl individuelle als auch Haushaltscharakteristika eine wichtige Rolle für Lohntransitionen. Letztlich zeigen die Ergebnisse große Unterschiede zwischen den europäischen Ländern, die sich teilweise auf die institutionellen Gegebenheiten der nationalen Arbeitsmärkte zurückführen lassen.
Keywords: J6; J31; P52; 330; wage inequality; wage mobility; wage transitions; cross-country analysis